Effect of Polytetrafluorethylene Content in Fe‐N‐C‐Based Catalyst Layers of Gas Diffusion Electrodes for HT‐PEM Fuel Cell Applications - Tanja Zierdt; Dr. Julia Müller‐Hülstede; Dr. Henrike Schmies; Dr. Dana Schonvogel; Peter Wagner; Prof. Dr. K. Andreas Friedrich (ChemElectroChem, 2024)
Abstract Fe‐N‐C catalysts are a promising alternative to replace cost‐intensive Pt‐based catalysts in high temperature polymer electrolyte membrane fuel cell (HT‐PEMFC) electrodes. However, the electrode fabrication needs to be adapted for this new class of catalysts. In this study, gas diffusion electrodes (GDEs) are fabricated using a commercial Fe‐N‐C catalyst and different polytetrafluorethylene (PTFE) binder ratios, varying from 10 to 50 wt % in the catalyst layer (CL). The oxygen reduction reaction performance is investigated under HT‐PEMFC conditions (160 °C, conc. H3PO4 electrolyte) in a half‐cell setup. The acidophilic character of the Fe‐N‐C catalyst leads to intrusion of phosphoric acid electrolyte into the CL. The strength of the acid penetration depends on the PTFE content, which is visible via the contact angles. The 10 wt % PTFE GDE is less capable to withdraw product water and electrolyte and results into the lowest half‐cell performance. Higher PTFE contents counterbalance the acid drag into the CL and impede flooding. The power density at around 130 mA mgCatalyst−2 increases by 34 % from 10 to 50 wt % PTFE.